New intraoperative imaging technologies: Innovating the surgeon's eye toward surgical precision. Issue 2 (4th August 2018) - Mascagni, Pietro; Longo, Fabio; Barberio, Manuel; Seeliger, Barbara; Agnus, Vincent; Saccomandi, Paola; Hostettler, Alexandre; Marescaux, Jacques; Diana, Michele
Abstract : Imaging is one of the pillars for the ongoing evolution of surgical oncology toward a precision paradigm. In the present overview, some established or emerging intraoperative imaging technologies are described in light of the vision and experience of our group in image‐guided surgery, focusing on digestive surgical oncology.